Neuroprotective Properties of a Standardized Extract from Myracrodruon urundeuva Fr. All. (Aroeira-Do-Sertão), as Evaluated by a Parkinson's Disease Model in Rats - Calou, Iana (Hindawi Publishing Corporation, 2014)
Myracrodruon urundeuva Fr. All. (Anacardiaceae) is a Brazilian medicinal species, which is common to the Northeastern Brazilian semiarid region, whose stem-bark is widely used in folk medicine. It is an endangered species, presenting as main bioactive components tannins and chalcones. In this work, we studied the neuroprotective effects of a standardized extract from cultivated M. urundeuva (SEMU), in a model of Parkinson's disease. Thus, a unilateral injection of 6-OHDA was done into the rat right stratum. The animals were submitted to stereotaxic surgery, then treated with SEMU (5, 10, 20, or 40 mg/kg, p.o.) for 2 weeks, subjected to behavioral tests, and euthanized for striata dissections and neurochemical, histological, and immunohistochemical analyses. We showed, for the first time, that SEMU reverted behavioral alterations seen in the 6-OHDA-lesioned group and partially blocked the decrease in DA and DOPAC contents. The numbers of viable neurons and TH immunopositive cells were increased by SEMU. In addition, the SEMU-treated 6-OHDA groups showed lower numbers of GFAP and OX-42 immunopositive cells. The neuroprotective action of SEMU is possibly related to the antioxidant and anti-inflammatory properties of M. urundeuva, pointing out to its potential use in the prevention or treatment of neurodegenerative conditions, such as Parkinson's disease.